Rare association between giant-cell aortitis and giant-cell aortic valvulitis - Jadán Luzuriaga, Georgina del Cisne; Dias, Ricardo Ribeiro; Santiago, José Augusto Duncan; Madrini Junior, Vagner; Ishikawa, Walther Yoshiharu; Fabio Fernandes,; Aiello, Vera Demarchi (Autopsy and Case Reports, 2023)
Giant cell arteritis (GCA) is a type of chronic vasculitis that affects medium and large-caliber arteries, frequently related to aortic involvement and, consequently, to aneurysm formation. However, associated valvulitis with giant cells is uncommon. We describe the case of a 50-year-old female patient with aortic aneurysm and valvular insufficiency, whose anatomopathological examination revealed giant-cell aortic valvulitis associated with giant cell aortitis.